DEVELOPING FIJI: MEASURING THE CONCERNS OF PRE-SERVICE STUDENTS FOR ICT IN EDUCATION - Dubey, Akash D; Alam, Mumtaz (European Scientific Journal, ESJ, 2014)
The intrusion of technologies in our daily lives has increased the competition in almost all the fields and due to this, the scholars of the present times are expected to be equipped with better problem solving skills, technofriendly nature and critical analysis abilities. In order to provide the necessary guidance to the students of modern times, it is necessary for the teachers to encourage the students to opt for more technical approach in the studies. The approach of the teachers, however, does not seem to be one minded. While some of them have accepted the changes in conventional teaching methods whole heartedly, there are still some who have out rightly rejected the idea of this change. In this research, we have analyzed the approach of the pre-service students who are pursuing bachelor of education in Social Science from Fiji National University, one of the leading universities of Republic of Fiji. For this analysis, we have used CBAM model which has been widely used since years for measuring concerns of people regarding the changes in the working environment. In our analysis, it was concluded that the pre-service students had high concerns at the Selforiented levels while a very low concern was shown at the external levels (Consequence, Collaboration and Refocusing). We have also pointed out some of the solutions that can lead these students to develop their concerns from internal level to external levels.